Digital Game Visual Style Classification: Influence of Information Quality Components on the User Satisfaction during Game Searching Activity in the Digital Game Library - Jamal, Jazmi Izwan; Mohd Yusof, Mohd Hafizuddin; Lim, Kok Yoong (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The digital gaming community appreciates the visual style classification system to search for information about a game product. However, scholars have discovered that the applied visual style classification system frequently leads to frustration and dissatisfaction among users owing to inaccurate search results. Moreover, there are yet any research studies that accurately measure user satisfaction during game searching activity in the digital game library based on the current visual style classification system. Therefore, this study was performed to investigate the influence of information quality components (Accuracy, Content, Ease of Use, Format, and Timeliness) on User Satisfaction during game searching activity in the digital game library. A cross-sectional study was conducted by distributing self-administered digital questionnaires to 239 game players in Malaysia. The 12-item instrument survey questionnaire, which consists of four main sections, adopted the End-user Computing Satisfaction (EUCS) model to examine the relationships between user satisfaction and information quality components. The results were then analysed using descriptive statistics, preliminary data analysis, and Confirmatory Factor Analysis (CFA). Based on the findings, more than half of the respondents were male (n = 139, 58.2%) with an age range between 19 and 24 years old, and 79.1% (n = 189) have experience in searching digital games based on visual styles. The EUCS model revealed that user satisfaction during game searching activity using the visual style information highly correlated with Content, Accuracy, and Ease of Use. Users were satisfied when they receive accurate, precise, and sufficient information. In addition, a user-friendly and simplified navigation interface improved the searching experience and stimulate users to further their searching activity. In contrast, the Format and Timeliness showed a weak correlation. Providing visual classification and appeal format has less impact on user satisfaction. In addition, the fast speed of information retrieval and up-to-date information showed an insignificant contribution to user satisfaction. Overall, this research demonstrated that information quality components, namely Content, Accuracy, and Ease of Use, influenced User Satisfaction when searching for games based on the visual style. Future studies should explore and evaluate the effectiveness of visual style information systems for digital game distribution platforms in Malaysia.